POLA KOMUNIKASI ANTARUMAT BERAGAMA DALAM MENCIPTAKAN KERUKUNAN DI MAHA VIHARA DUTA MAITREYA KOTA BATAM - Agustina, Risma Maya; Rorong, Michael Jibrael (LPPM Universitas Putera Batam, 2023)
Communications is one of the normal things for humans life. The result of this research is that the pattern ofinter-religious communications formed at Maha Vihara Duta Maitreya Batam uses personal communicationsand gorup communication with the aim of maintaining inter-religious tolerance in communcating with theestablishment of this communication.namely the occurence of two-way communication and the occurence offeedback between the sender of the message and the recipient of the message. In this communication pattern,communication is established between religious communities at the Maha Vihara Duta Maitreya, which iscreated at major monastic events such as Chinese New Year Celebrations, Vesak, and Moon Cake events